2018
DOI: 10.1111/bjd.16807
|View full text |Cite
|
Sign up to set email alerts
|

A traditional Chinese remedy points to a natural skin habitat: indirubin (indigo naturalis) for psoriasis and the Malassezia metabolome

Abstract: Linked Article: Lin et al. Br J Dermatol 2018; 178:124–31.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Ambient environmental conditions and host factors (hygiene, genetic predisposition, age and immune status) can cause shifts in skin microbial communities and induce Malassezia ‐associated diseases . Malassezia , apart from Malassezia folliculitis, causes seborrhoeic dermatitis (SD), pityriasis versicolor (PV), aggravates the head and neck variant of atopic dermatitis and is recently suggested to participate in psoriasis through mechanisms that include aryl hydrocarbon receptor downstream pathways . Malassezia yeasts have been also associated with catheter‐related fungemia, sepsis and invasive infections in immunocompromised patients on parenteral nutrition …”
Section: Resultsmentioning
confidence: 99%
“…Ambient environmental conditions and host factors (hygiene, genetic predisposition, age and immune status) can cause shifts in skin microbial communities and induce Malassezia ‐associated diseases . Malassezia , apart from Malassezia folliculitis, causes seborrhoeic dermatitis (SD), pityriasis versicolor (PV), aggravates the head and neck variant of atopic dermatitis and is recently suggested to participate in psoriasis through mechanisms that include aryl hydrocarbon receptor downstream pathways . Malassezia yeasts have been also associated with catheter‐related fungemia, sepsis and invasive infections in immunocompromised patients on parenteral nutrition …”
Section: Resultsmentioning
confidence: 99%
“…In the skin, indirubin was shown to attenuate psoriasis-like skin lesions in imiquimod-induced and Stat3-transgenic mouse models 6,7 . Topical application of indirubin also improved human psoriasis in a clinical trial without causing serious adverse events 8,9 . Indirubin is known to exert its biological function via xenobiotic aryl hydrocarbon receptor (AHR) 10 .…”
Section: Introductionmentioning
confidence: 92%
“…With the advantage of being generally safe and having few side effects, great attention has been paid to natural products in the past few decades [ 8 , 9 ]. Indirubin (IR), isolated from indigo naturalis, has been shown to improve psoriasis without causing any serious adverse events [ 10 , 11 ]. Previous studies have shown that IR could alleviate psoriasis via regulation of keratinocyte proliferation and reduces inflammatory processes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%